2020
DOI: 10.1002/bio.3958
|View full text |Cite
|
Sign up to set email alerts
|

An electrogenerated chemiluminescence aptasensor for lysozyme based on the interaction between Ru(bpy)32+ and cucurbit[8]uril

Abstract: Strong anodic Ru(bpy)32+ electrogenerated chemiluminescence (ECL) was obtained at a cucurbil[8]uril (CB[8]) modified electrode in neutral conditions without the need of an additional coreactant. An ECL aptasensor was fabricated based on the strong ECL emission as well as the host–guest interaction between DNA and CB[8]. Firstly, amino group‐terminated complementary DNA (DNA‐NH2) was firmly immobilized on CB[8]/glass carbon electrode, which could further increase ECL intensity. Then, a ferrocene group‐terminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Aptamers are single-stranded DNA or RNA oligonucleotides with high specificity and affinity for target substances screened from random oligonucleotide libraries based on Systematic Evolution of Ligands by EXponential enrichment (SELEX). [9][10][11] As an excellent tool of biological science, the aptamer has been widely used in the detection of cells, viruses, proteins, toxins, allergens, and other biological components because of its high affinity, strong specificity, large surface area, a large number of receptor binding sites, and a wide range of targets. [12][13][14] Catalytic hairpin assemblies (CHA), as a mature enzyme-free DNA amplification technique with high efficiency and target cycle, have been applied in the field of signal transduction and amplification related to nucleic acid analysis and biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are single-stranded DNA or RNA oligonucleotides with high specificity and affinity for target substances screened from random oligonucleotide libraries based on Systematic Evolution of Ligands by EXponential enrichment (SELEX). [9][10][11] As an excellent tool of biological science, the aptamer has been widely used in the detection of cells, viruses, proteins, toxins, allergens, and other biological components because of its high affinity, strong specificity, large surface area, a large number of receptor binding sites, and a wide range of targets. [12][13][14] Catalytic hairpin assemblies (CHA), as a mature enzyme-free DNA amplification technique with high efficiency and target cycle, have been applied in the field of signal transduction and amplification related to nucleic acid analysis and biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some preliminary investigations have been carried out in our laboratory, and it was found that Q[ n ]s could enhance the Ru(bpy) 3 2+ ECL intensity, which was used to detect lysozyme. 26 However, there are few reports about the application of Q[ n ]s in fabricating ECL sensors, and further applications of Q[ n ]s in ECL still need to be explored.…”
Section: Introductionmentioning
confidence: 99%